Phenolic compounds: Evidence for inhibitory effects against obesity and their underlying molecular signaling mechanisms - Hsu, Chin-Lin; Yen, Gow-Chin (Molecular nutrition & food research, 2008)
Phenolic compounds are widely present in the plant kingdom. Many epidemiological studies have indicated that consumption of some plant-derived foodstuffs with high phenolic content is associated with the prevention of some diseases and that these compounds may have similar properties to antioxidants, antimutagenic agents, antithrombotic agents, anti-inflammatory agents, anti-HIV-1, and anticancer agents. However, obesity is an important topic in the world of public health and preventive medicine. Relationships between body mass index, waist circumference, or waist-to-hip ratio and the risk of development of some diseases (such as heart disease, dyslipidemia, hypertension, non-alcoholic fatty liver disease, diabetes, kidney failure, cancer, stroke, osteoarthritis, and sleep apnea) have been observed. Evidence that phenolic compounds have beneficial effects in fighting obesity is increasingly being reported in the scientific literature. These in vitro and in vivo effects of phenolic compounds on the induction of pre-adipocytic and adipocytic apoptosis and inhibition of adipocytic lipid accumulation are considered in detail here. This review presents evidence of their inhibitory effects on obesity and their underlying molecular signaling mechanisms.